Association of Hashimoto thyroiditis with papillary thyroid carcinoma and its clinical features – A retrospective study in a tertiary care hospital - Pradhan, Rajashree; Goswami, Chirasri; Sikder, Mrinal; Upasana Mukherjee; Mondal, Sajeeb (Asian Journal of Medical Sciences, 2024)
Background: Papillary thyroid carcinoma (PTC) is the most widespread endocrine malignancy. Among the several risk factors, Hashimoto thyroiditis (HT) is one of the factors associated with increased incidence of PTC. Both HT and PTC share several epidemiologic features including high prevalence, female predominance, and increased incidence in iodine-sufficient areas. Aims and Objectives: The aim of the study was to assess the incidence of HT and PTC coexistent in endemic population. The study also aimed to determine the association of various prognostic parameters of PTC in patients with coexistent HT. Materials and Methods: This was a retrospective study done from May 2019 to May 2024 over a period of 5 years in a tertiary care hospital of West Bengal. A total of 54 patients with primary PTC who underwent total thyroidectomy with cervical lymph node dissection (LND) were studied. Patients with primary PTC with neck LND and complete medical history were included in this study. Patients with previous thyroidectomy surgery or patients with incidental PTC diagnosed in thyroidectomy specimens done for a benign neoplasm (without LND) were excluded from the study. Results: A total of 54 cases of PTC were studied out of which 23 cases were PTC associated with HT and 31 cases were PTC without HT constituting 42.59% and 57.4%, respectively. PTC associated with HT had a greater incidence in females. In this study, our results showed that PTC with HT had a greater tendency of tumor multifocality, greater mean lymph node size, and increase rate of extranodal tumor extension. At the same time, patients of PTC associated with HT had smaller tumor size and low clinical stage. Conclusion: PTC associated with HT had a female preponderance, larger metastatic lymph node, a tendency for multifocality, and extranodal extension. At the same, they also had smaller tumor size and low clinical stage indicating a complex and controversial effect of HT on PTC.